Perancangan Sistem Pendukung Keputusan Penerima Bantuan Sosial Menggunakan Metode Simple Additive Weighting (SAW) Berbasis Web - Achmad Rizaldy (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Social assistance is assistance in the form of money, goods, or services provided to individuals, families, groups or the poor as an effort to improve the welfare of the community. The provision of social assistance is carried out by providing non-continuous and selective assistance to underprivileged communities. However, in the distribution of social assistance, a problem arises where the decision-making for the selection of recipients of social assistance is more subjective due to the proximity of the RT apparatus to its citizens. Another problem is that due to the large number of existing citizen data, there are some citizen data that have not been selected properly and systematically. This causes the distribution of social assistance to be not well targeted. Therefore, a research was conducted on the design of a decision support system for social assistance recipients. This study resulted in a Decision Support System using the Simple Additive Weighting method which can help select residents who are eligible to receive social assistance. The system created using the method can provide an assessment of prospective social assistance recipients so that decision making on the selection of social assistance recipients becomes more objective and on target. With the Simple Additive Weighting (SAW) design which was made specifically to process citizen data thoroughly and quickly, all residents can be selected properly and systematically. Keywords: Social assistance, Decision making, Simple Additive Weighting, SAW.